VALIDITAS DAN RELIABILITAS ANGKET MOTIVASI BERPRESTASI - Riko Al Hakim; Ika Mustika; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
Achievement motivation has an important role in education, besides acting as an encouragement for students to achieve optimal achievement, achievement motivation also plays a role as a determinant of learning outcomes and student learning achievements. Therefore, it is necessary to measure achievement motivation in the form of a achievement motivation questionnaire that has gone through the validity test stage and the reliability test stage. The subjects in this study were students of SMK 01 Cipongkor class XII totaling 20 students. From the results of the validity test of 38 statements there are 30 questions that are declared valid and the validity test gets a value of 0.941 which means it is included in the very high category. Thus the achievement motivation questionnaire can be used as a tool to measure the level of achievement motivation of students. Keywords:  Achievement Motivation,  Validity and Reliability